Fast kinetics of calcium liberation induced in Xenopus oocytes by photoreleased inositol trisphosphate. - Parker, I (1996)
Inositol 1,4,5-trisphosphate (InsP3) acts on intracellular receptors to cause liberation of Ca2+ ions into the cytosol as repetitive spikes and propagating waves. We studied the processes underlying this regenerative release of Ca2+ by monitoring with high resolution the kinetics of Ca2+ flux evoked in Xenopus oocytes by flash photolysis of caged InsP3. Confocal microfluorimetry was used to monitor intracellular free [Ca2+] from femtoliter volumes within the cell, and the underlying Ca2+ flux was then derived from the rate of increase of the fluorescence signals. A threshold amount of InsP3 had to be photoreleased to evoke any appreciable Ca2+ signal, and the amount of liberated Ca2+ then increased only approximately fourfold with maximal stimulation, whereas the peak rate of increase of Ca2+ varied over a range of nearly 20-fold, reaching a maximum of approximately 150 microMs-1. Ca2+ flux increased as a first-order function of [InsP3]. Indicating a lack of cooperativity in channel opening, and was half-maximal with stimuli approximately 10 times threshold. After a brief photolysis flash, Ca2+ efflux began after a quiescent latent period that shortened from several hundred milliseconds with near-threshold stimuli to 25 ms with maximal flashes. This delay could not be explained by an initial "foot" of Ca2+ increasing toward a threshold at which regenerative release was triggered, and the onset of release seemed too abrupt to be accounted for by multiple sequential steps involved in channel opening. Ca2+ efflux increased to a maximum after the latent period in a time that reduced from > 100 ms to approximately 8 ms with increasing [InsP3] and subsequently declined along a two-exponential time course: a rapid fall with a time constant shortening from > 100 ms to approximately 25 ms with increasing [InsP3], followed by a much smaller fail persisting for several seconds. The results are discussed in terms of a model in which InsP3 receptors must undergo a slow transition after binding InsP3 before they can be activated by cytosolic Ca2+ acting as a co-agonist. Positive feedback by liberated Ca2+ ions then leads to a rapid increase in efflux to a maximal rate set by the proportion of receptors binding InsP3. Subsequently, Ca2+ efflux terminates because of a slower inhibitory action of cytosolic Ca2+ on gating of InsP3 receptor-channels.